Rancang Bangun Sistem Informasi Pergudangan Berbasis Web - Hermanto; Siti Khalimah (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2020)
Abstract At this time warehousing data processing at PT. Ravana Jaya is still done using Microsoft Excel, so the performance process has not been effective. Therefore, the purpose of this study is to design a web-based warehousing information system at PT. Ravana Jaya Gresik and implement it. This information system was built and designed using Notepad ++ version 2, XAMPP version 1.8.1, PHP version 5.4.7, MySQL version 5.5.27, and Apache version 2.4.3.The data collection process is carried out using a system analysis method that has been running at PT. Ravana Jaya then carried out the system design stage which was used to meet the system needs. Making this system can help companies by changing the data processing system that has been running using Excel to become a web-based data processing system. The results of this study are a web-based warehousing information system that can manage inventory data efficiently and quickly.   Keyword : Warehousing, Information System, Web-Based